A domestic pressure cooker mediated, facile autoclaving method for the synthesis of silver nanoparticles - Aruna Jyothi Kora (MethodsX, 2023)
As an alternative to an expensive hydrothermal reactor, in the current method a domestic pressure was used for the synthesis of silver nanoparticles (Ag NP) using tree gum, kondagogu as dual functional reductant and stabilizer by autoclaving. The formation of Ag NP was evaluated with colour transformation, UV-Visible spectroscopy (UV–Vis) and transmission electron microscopy. The formation of Ag NP by gum confirmed from the developed yellow coloration of the solution and the appearance of surface plasmon resonance peak at 408 nm in the UV–Vis. The produced NP were spherical, polydisperse, particle size ranged from 2.9–17.6 nm and the average particle size was 4.5 ± 3.1 nm. The developed method is useful for demonstration, gaining hands on experience and production of metal and metal oxide NP in resource limited small laboratories, rural colleges, startups etc. • Pressure cooker serves as an easily accessible, durable, inexpensive, electricity independent hydrothermal nanoparticle production vessel. • Autoclaving serves as a facile, ecofriendly, less energy consuming, one pot, green method with dual functional role of in situ nanoparticle synthesis and sterilization. • Production of intrinsically safe and sterile nanoparticles amenable for in vivo and in vitro biomedical applications.